Reconstruction of healed elongated anterior tibial and extensor hallucis longus tendons in a young active farmer. Issue 3 (September 2015) - Wong-Chung, John; Lynch-Wong, Matthew; Gibson, Desmond; Stokes, Michael
Highlights A primary end-to-end repair of an open laceration of anterior tibial tendon failed. The tendon healed in continuity but in elongated position with resultant foot drop. Postoperative immobilization following anterior tibial tendon repair is discussed. A technique for reconstructing a healed elongated anterior tibial tendon is presented.